Skeletal muscle mitochondrial capacity in people with multiple sclerosis. (November 2016) - Harp, Mary Ann; McCully, Kevin K; Moldavskiy, Marina; Backus, Deborah
Background: People with multiple sclerosis (MS) have functional disability and may have reduced muscle mitochondrial capacity. Objective: The objective of this paper is to measure muscle mitochondrial capacity of leg muscles using near-infrared spectroscopy (NIRS) and compare to functional status. Materials and methods: People with MS ( n  = 16) and a control (CON) group ( n  = 9) were evaluated for 25-ft walk time. Mitochondrial capacity of both gastrocnemius muscles were measured with NIRS as the rate of recovery of oxygen consumption in after exercise. Results: Mitochondrial capacity was lower in the MS group compared to the CON group (rate constants: 1.13 ± 0.29 vs. 1.68 ± 0.37 min −1, p  < 0.05). There was a tendency for people with MS who used assistive devices to have lower mitochondrial capacity in the weaker leg ( p  = 0.07). Conclusion: NIRS measurements of mitochondrial capacity suggest a 40% deficit in people with MS compared to CONs and this may contribute to walking disability.